PERANCANGAN WEBSITE PAROKI SANTO LUKAS - Yosep, Dicky; Rusdi, Zyad (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
The Information Website is a common item within the globalization era nowadays. With the example of the Church Website of Santo Lukas Church. The purpose in making the Church Website is to spread the information of the religious actions to the member of the church and communication between the users. Santo Lukas Church Website will have the simple forum inside and also having the simple short messaging for communication purpose. The design is done using the PHP programming language, MySQL as its database. Testing applications using the White Box Testing and Black Box Testing. The test results for all modules in accordance with design specifications and no error message.